Peritumoral Microgel Reservoir for Long-Term Light-Controlled Triple-Synergistic Treatment of Osteosarcoma with Single Ultra-Low Dose - Yan Jiaqi; Wang Yichuan; Ran Meixin; Mustafa Rawand A.; Luo Huanhuan; Wang Jixiang; Smått Jan-Henrik; Rosenholm Jessica M.; Cui Wenguo; Lu Yong; Guan Zhenpeng; Zhang Hongbo (WILEY-V C H VERLAG GMBH, 2025)
Local minimally invasive injection of anticancer therapies is a compelling approach to maximize the utilization of drugs and reduce the systemic adverse drug effects. However, the clinical translation is still hampered by many challenges such as short residence time of therapeutic agents and the difficulty in achieving multi-modulation combination therapy. Herein, mesoporous silica-coated gold nanorods (AuNR@SiO2) core-shell nanoparticles are fabricated to facilitate drug loading while rendering them photothermally responsive. Subsequently, AuNR@SiO2 is anchored into a monodisperse photocrosslinkable gelatin (GelMA) microgel through one-step microfluidic technology. Chemotherapeutic drug doxorubicin (DOX) is loaded into AuNR@SiO2 and 5,6-dimethylxanthenone-4-acetic acid (DMXAA) is loaded in the microgel layer. The osteosarcoma targeting ligand alendronate is conjugated to AuNR@SiO2 to improve the tumor targeting. The microgel greatly improves the injectability since they can be dispersed in buffer and the injectability and degradability are adjustable by microfluidics during the fabrication. The drug release can, in turn, be modulated by multi-round light-trigger. Importantly, a single super low drug dose (1 mg kg(-1) DOX with 5 mg kg(-1) DMXAA) with peritumoral injection generates long-term therapeutic effect and significantly inhibited tumor growth in osteosarcoma bearing mice. Therefore, this nanocomposite@microgel system can act as a peritumoral reservoir for long-term effective osteosarcoma treatment.